Medical Education Transformation: Lifestyle Medicine in Undergraduate and Graduate Medical Education, Fellowship, and Continuing Medical Education. Issue 5 (September 2021) - Rea, Brenda; Worthman, Shannon; Shetty, Paulina; Alexander, Megan; Trilk, Jennifer L.
A gaping void of adequate lifestyle medicine (LM) training exists across the medical education continuum. The American College of Lifestyle Medicine's (ACLM's) undergraduate medical education (UME) Task Force champions the need for widespread integration of LM curriculum in UME by sharing ideas for catalyzing success, lessons learned, and publishing standards and competencies to facilitate curriculum reform. When it comes to graduate medical education and fellowship, the ACLM and American Board of Lifestyle Medicine have made great strides in filling the void, developing both Educational and Experiential Pathways through which physicians may become certified LM Physicians or LM Specialists (LMSs). The Lifestyle Medicine Residency Curriculum meets the Educational Pathway requirements and prepares resident graduates for the LM Physician board certification. LMS is the second tier of LM certification that demonstrates expertise in disease reversal. The LMS Fellowship is an Educational Pathway intent on American Board of Medical Specialties recognition of LM as a new subspecialty in the near future. Finally, continuing medical education and maintenance of certification equip physicians with LM training to support knowledge, application, and certification in LM.